Analysis and suggestions on the development of IoT technology - Wenke YU; Yuan CHENG; Fang LI; Qi ZHAO (物联网学报)
The Internet of things (IoT) has been developing for a decade in China,which has rapidly evolved from the early sensor network technology,radio frequency identification (RFID) technology to the intelligent networking technology based on 5G.The Internet of everything is coming to our life.The application of IoT has also been gradually and comprehensively applied in from the area of financial IC card to the industry,government affairs,transportation,health care,education,and etc.The development of the IoT hot technologies represented by 5G and low-power wide-area network (LPWAN),and the deep integration of blockchain,edge computing and other technologies with the IoT,comprehensively promote the deep application of the IoT in the industry,which brings great development opportunities to all the industry.It was focused on the analysis of the status of 5G,IoT identification,edge computing,LPWAN,security technology,and etc.The development tendency of the IoT was also forecasted,and the corresponding policy suggestion to promote the development of IoT was put forward.